Model of Waqf Based Business Units Solution for Poverty Alleviation in Indonesia (The Case of Pesantren Gontor Ponorogo, East Java) - Andi Triyawan (Universiti Sains Islam Malaysia, 2024)
Matric: 4201011 (FEM)